Formation of Communicative Competence of Primary Class Students Based on Didactic Game Technology - Arman Rsaliev (Genius Journals, 2023)
This article describes how important and effective didactic game technologies are for the learning process in primary education, as well as the theoretical basis for the formation of didactic games' communication content in education.
Keywords: didactic game; communication; communicative competence